Healing and Deliverance in Church Growth: The Case of the Global Evangelical Church, Ghana from 1991-2011 - Ahiabu, Y.K. (University of Ghana, 2013)
Healing and deliverance has become very common and central to the activities of most churches in Ghana. The Global Evangelical Church (GEC) is one of the churches in Ghana that engages in the practice. The Church has since its inception in 1991 engaged in healing and deliverance as part of its theological orientation. This practice has been incorporated into the church with the aim of evangelizing people as well as responding to the needs of its members and the general society. Consequently, healing and deliverance is considered as playing a significant role towards the growth of the church. With specific focus on the GEC, this research, investigates the practice of healing and deliverance and the extent to which it has enhanced the growth of the (GEC). The purpose of this research is to understand the relationship between 'healing and deliverance' and church growth in the GEC. Employing phenomenological and historical methods, which include the use of scholarly and non- scholarly books on healing, deliverance and church growth, data was collected through interviews, focus group discussions and participants’ observation from three congregations of the GEC. Using qualitative method of data analysis, views elicited from the field have been discussed in the light of scholarly perspectives on elements of healing and deliverance and principles of church growth. It was discovered that healing and deliverance, as a practice, is characterised by different activities. It is the effectiveness of these activities that contributes to the well-being of the ‘healed’ and ‘delivered’. The practice has also been used as an evangelistic tool in winning many souls into the church and subsequently leads to numerical, conceptual, incarnational, financial and infrastructural growth of the church. This research has also found that healing and deliverance has contributed greatly to the growth of the Global Evangelical Church within the period under-studied. The study has discovered that healing and deliverance is a factor but not the only factor and does has positive correlation with the growth of the congregations studied.
Thesis (MPHIL)-University of Ghana, 2013